EVALUATION OF MEASLES PREVENTION EFFECTIVENESS THROUGH VACCINATION IN THE KHOREZM REGION - Masharipova , Shakhista (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
Measles remains one of the most contagious viral infections worldwide, posing a persistent public health challenge despite the availability of safe and effective vaccines. Ensuring adequate vaccination coverage and monitoring post-vaccination immunity are essential to maintaining epidemiological stability and achieving sustainable herd immunity. Regional assessments of immunization effectiveness provide important evidence for strengthening national immunization strategies.This study aimed to analyze the effectiveness of measles prevention through vaccination in the Khorezm region. An analytical cross-sectional study was conducted during 2024–2025 to evaluate post-vaccination immune response and the overall effectiveness of specific prophylaxis. The level of protective IgG antibodies against measles virus was determined using enzyme-linked immunosorbent assay (ELISA). A threshold of ≥200 mIU/mL was considered indicative of protective immunity. Statistical analysis was performed using standard epidemiological methods, including calculation of percentages, confidence intervals, and significance testing.